Flipped Peer Teaching as Part of Active Learning Activities for Process Optimization Subject - Jamaludin, Nabila Farhana; Hadipornama, Muhammad Fairis; Samaae, Maisaroh (Semarak International Journal of STEM Education, 2025)
Traditional lecture-based methods in engineering education often lead to passive learning, limiting student engagement and the ability to apply complex concepts in practice. This study investigates the implementation of flipped peer teaching (FPT) as an active learning strategy in a Process Optimization course for final-year chemical engineering students. Flipped peer teaching integrates flipped classroom and peer teaching approaches, requiring students to engage with learning materials independently before teaching their peers in structured class sessions. The methodology involved five phases: lecturer preparation, pre-class student preparation, lecturer guidance and review, in-class peer teaching implementation, and post-class feedback collection. Findings showed that 83.3% of students found preparing and delivering teaching materials more effective than conventional lectures for understanding course content. Additionally, 66.7% reported increased confidence in applying concepts during assessments, and 62.5% found peer teaching sessions more engaging than traditional lectures. However, effectiveness ratings varied, with 50% rating the sessions as moderately effective and 41.7% as very effective. Overall, the flipped peer teaching model enhanced student engagement, conceptual understanding, and communication skills, though its integration alongside traditional teaching is recommended to support diverse learner needs. This study contributes to pedagogical innovations in engineering education by demonstrating the feasibility and benefits of flipped peer teaching for technical subject mastery.